2020
DOI: 10.1007/s12519-020-00345-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment recommendations for pediatric respiratory infection caused by the 2019 novel coronavirus

Abstract: Since December 2019, an epidemic caused by novel coronavirus (2019-nCoV) infection has occurred unexpectedly in China. As of 8 pm, 31 January 2020, more than 20 pediatric cases have been reported in China. Of these cases, ten patients were identified in Zhejiang Province, with an age of onset ranging from 112 days to 17 years. Following the latest National recommendations for diagnosis and treatment of pneumonia caused by 2019-nCoV (the 4th edition) and current status of clinical practice in Zhejiang Province,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
673
4
108

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(808 citation statements)
references
References 7 publications
23
673
4
108
Order By: Relevance
“…A recent study in Beijing reported that 2 of the 13 patients with SARS-CoV-2 pneumonia were children aged between 2-15 years [9] . As of 10 February 2020, more than 20 paediatric cases have been reported in China, 10 of whom were identified in Zhejiang Province and were in the age range of 112 days to 17 years [31] . Among adult patients, cardiovascular disease and hypertension were the most common underlying diseases, followed by diabetes mellitus.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…A recent study in Beijing reported that 2 of the 13 patients with SARS-CoV-2 pneumonia were children aged between 2-15 years [9] . As of 10 February 2020, more than 20 paediatric cases have been reported in China, 10 of whom were identified in Zhejiang Province and were in the age range of 112 days to 17 years [31] . Among adult patients, cardiovascular disease and hypertension were the most common underlying diseases, followed by diabetes mellitus.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Possible reasons for these findings are as follows: 1) adolescent cases are mostly third-generation infection cases, which may involve mainly family cluster cases. Furthermore, COVID-19 has weak virulence, resulting in lighter imaging signs in these patients [7] ; 2) minors have immature lung structure development, resulting in atypical HRCT signs, and; 3) a COVID-19 attack on the immune system is more likely to cause diffuse alveolar damage and a large number of inflammatory exudations in middle-aged and older patients with more baseline diseases. In one patient, bilateral pleural effusion was found, which may be due to the adjacent inflammation stimulating the pleura.…”
Section: Covid-19 Infection and Distinguished Imaging Signs Between Pmentioning
confidence: 99%
“…Studies have shown that, compared to middle-aged and elderly people with COVID-19 infection, children or young people have milder symptoms, are more easily cured, and have a good prognosis [7] . In this study, we analyzed the HRCT lung manifestations and related signs in 98 patients of different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Los casos pediátricos publicados son, hasta la fecha, escasos 8,9 y parece que más leves especialmente en lactantes 19 . El periodo de incubación se encuentra entre 2-14 días (mediana 3-7 días).…”
Section: Cuadro Clínico De La Infección Respiratoria Covid-19unclassified
“…(1-2 mg/kg/día) durante 3 a 5 días, pero no para uso a largo plazo 8,9 . Se han empleado inmunoglobulinas intravenosas en casos graves, pero su indicación y eficacia debe ser evaluada.…”
Section: Corticoides Sistémicos E Inmunomoduladoresunclassified